Cognitive plasticity in neurologic disorders - Tracy, Joseph I.; Hampstead, Benjamin M.; Sathian, K. (Oxford University Press, USA, 2014)
Cognitive Plasticity in Neurologic Disorders describes and specifies the cognitive impact of neuroplastic processes in key neurologic disorders and syndromes. It is set apart from previous works in this area by its emphasis on the changing quality of neurocognition, demonstrating that this dynamic nature emerges from the neuroplastic processes at work in both mild and severe states of brain disease or injury. This resource describes the ways neurological illness or trauma (or attempts to treat patients with such conditions) can trigger neuroplastic mechanisms in the brain, inducing cognitive r.